2013
DOI: 10.1002/14651858.cd001318.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for cervical intraepithelial neoplasia

Abstract: Background-Cervical intraepithelial neoplasia (CIN) is the most common pre-malignant lesion. Atypical squamous changes occur in the transformation zone of the cervix with mild, moderate or severe changes described by their depth (CIN 1, 2 or 3). Cervical intraepithelial neoplasia is treated by local ablation or lower morbidity excision techniques. Choice of treatment depends on the grade and extent of the disease.Objectives-To assess the effectiveness and safety of alternative surgical treatments for CIN.Searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(94 citation statements)
references
References 59 publications
(92 reference statements)
2
88
0
4
Order By: Relevance
“…The two test methods evaluated in our study, hc2 and RealTime, were shown to have clinical sensitivity and specificity of 100 and 78.8 % (hc2)/specificity 84. 8 [17,18,22]). Similar to our findings these studies also found a tendency towards higher specificity for RealTime compared to hc2 and higher clinical sensitivity for hc2.…”
Section: Hpv Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The two test methods evaluated in our study, hc2 and RealTime, were shown to have clinical sensitivity and specificity of 100 and 78.8 % (hc2)/specificity 84. 8 [17,18,22]). Similar to our findings these studies also found a tendency towards higher specificity for RealTime compared to hc2 and higher clinical sensitivity for hc2.…”
Section: Hpv Statusmentioning
confidence: 99%
“…Loop excision is the most commonly used method, which, in contrast to e.g. laser ablation, allows acquisition of a cone biopsy for histological analysis and assessment of endo-and ectocervical resection margins [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical carcinogenesis is a very slow process that lasts approximately 15-30 years from initial hrHPV infection to cancer development [8]. This process is characterized by cytomorphologically recognizable premalignant stages, which can be adequately treated to prevent progression to cancer [9]. For these reasons, cervical cancer is an ideal screening target.…”
Section: Introductionmentioning
confidence: 99%
“…We must keep in mind that these patients are mostly of childbearing age and desire preservation of fertility. Repeated treatments on the cervix can cause negative sequelae in their reproductive health [3].…”
Section: Introductionmentioning
confidence: 99%